The impacts of bark harvesting on a population of Encephalartos transvenosus (Limpopo cycad), in Limpopo Province, South Africa - Samuel Bamigboye; M. PETER TSHISIKHAWE (Society for Indonesian Biodiversity, 2020)
Cycads are the most threatened group of plants in the world and there are a wide range of ecological and anthropological forces responsible for the extinction risk of these taxa. South Africa is a global hotspot of cycad diversity and the country’s cycads are facing high extinction risk. In this study we sampled a population (n=34) of Encephalartos transvenosus Stapf & Burtt Davy, a cycad species endemic to Limpopo Province, South Africa. The population was located on the Soutpansberg mountain range in the Mutale local municipality. A survey was conducted to quantify the threats to the population.  Forty-seven percent of the plants had been damaged by bark harvesting for traditional medicine, and the population showed a mortality rate of 9%. We recommend further studies at a range of Encephalartos transvenosus populations to provide a broader understanding of impacts of harvesting and population trends. We also recommend community based initiatives to enhance the protection of this species in the communities in which they are found.